ALTERNATE OPTIONS TO RICE (ORYZA SATIVA) – WHEAT (TRITICUM AESTIVUM) CROPPING SYSTEM FOR PARTIALLY RECLAIMED SODIC SOILS - SINGH, YASH PAL; MISHRA, VINAY KUMAR; KUMAR GUPTA, RAVINDRA (Innovare Journal of Agricultural Sciences, 2022)
Objectives: A field experiment was conducted during 2013–2014−2015–2016 at Central Soil Salinity Research Institute, Regional Research Station, experimental farm, Shivri, Lucknow to find out the alternate options to rice (Oryza sativa L.) – wheat (Triticum aestivum L.) cropping system in partially reclaimed sodic soils. Methods: Four cropping systems, namely, rice (O. sativa L.) – Wheat (T. aestivum L.) (Cereal-based), sorghum (Sorghum bicolor) – berseem (Trifolium alexandrinum) (Fodder-based), sweet basil (tulsi) (Ocimum basilicum L.) – matricaria (Matricaria chamomilla) (medicinal and aromatic crop-based), and chilli (Capsicum spp.) – garlic (Allium sativum Linn.) (spices-based) were evaluated in the light of sustainability, potentiality, and profitability. Results and Discussion: Maximum rice equivalent yield (14.21 t/ha) and production efficiency (61.25 kg/ha/day) were recorded with sweet basil– matricaria cropping system, whereas highest land use efficiency (78.35%) was observed under sorghum–berseem fodder-based cropping system. Highest water expense efficiency (150.72 kg/ha cm) was recorded with chilli–garlic cropping system followed by sweet basil–matricaria, but the total amount of water used was more (125.65 cm) in rice–wheat system. The water requirements of sorghum–berseem, sweet basil–matricaria, and chilli–garlic cropping systems were 8.0, 19.8, and 31.8% less than the rice–wheat cropping system. Among the cropping systems evaluated, maximum energy input (27.50 MJ/ha) and output (314.46 MJ/ha) were analyzed in rice–wheat system. Whereas, maximum energy use efficiency (11.99) was found with sweet basil–matricaria followed by sorghum–berseem (11.91) cropping systems. Highest soil ameliorative potential was established with sweet basil–matricaria cropping system than rest of the cropping systems. Highest net return (Rs. 63,222/ha) and benefit: cost ratio of 2.74 was deliberated with medicinal and aromatic crop-based sweet basil–matricaria cropping system than rest of the cropping systems. Conclusion: From the study, it is concluded that, diversification of rice–wheat cropping system with other highly remunerative crops such as sweet basil and chilli in kharif and matricaria and garlic in rabi is an alternate highly remunerative medicinal and aromatic and spices-based cropping systems which may be adopted by the farmers to get higher returns per unit area and to save the natural resources.